Detection of swine rotavirus and transmissible gastroenteritis virus in piglets with diarrhoea by sandwich ELISA - Barman, N N; Sarma, D K; Penseart, M (The Indian Journal of Animal Sciences, 2012)
The prevalence of rota virus (RV) and transmissible gastroenteritis virus (TGEV) in faeces of 1- to 8- week-old piglets with diarrohea was studied by enzyme-linked immunosorbent assay (ELISA). Of 126 diarrhoeic piglets, 34 ( 26.9%) were positive for RV and the highest incidence was recorded in 4-week-old piglets (53.1 %). None of the samples was found positive for TGEV.